Despair in Asian literature: exploring Dazai Osamu’s No Longer Human in the light of existentialism, absurdism & critical disability theory - Tofa, Halima Hasin (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2022.